Brief Cognitive Behavioral Therapy For Chronic Pain: Results From a Clinical Demonstration Project in Primary Care Behavioral Health. Issue 10 (October 2019) - Beehler, Gregory P.; Murphy, Jennifer L.; King, Paul R.; Dollar, Katherine M.; Kearney, Lisa K.; Haslam, Aaron; Wade, Michael; Goldstein, Wade R.
Abstract : Objectives: Although cognitive behavioral therapy is an effective intervention for chronic pain, it is a lengthy treatment typically applied only in specialty care settings. The aim of this project was to collect preliminary effectiveness data for Brief Cognitive Behavioral Therapy for Chronic Pain (Brief CBT-CP), an abbreviated, modular form of treatment designed for use in primary care. Methods: A clinical demonstration project was conducted in which Brief CBT-CP was delivered to primary care patients by 22 integrated care providers practicing in the Primary Care Behavioral Health model of Veterans Health Administration primary care clinics. Brief measures were used at each appointment to collect patient-reported clinical outcomes. Results: One hundred eighteen patients provided sufficient data for analysis (male, 75%; mean age, 51.4 y). Multilevel modeling suggested that a composite measure of pain intensity and functional limitations showed statistically significant improvements by the third appointment (Cohen's d =0.65). Pain-related self-efficacy outcomes showed a similar pattern of results but of smaller effect size (Cohen's d =0.22). The exploratory analysis identified that Brief CBT-CP modules addressing psychoeducation and goal setting, pacing, and relaxation training were associated with the most significant gains in treatment outcomes. Discussion: These findings provide early support for the effectiveness of Brief CBT-CP when delivered by providers in every day Primary Care Behavioral Health settings. Results are discussed in relation to the need for additional research regarding the potential value of employing safe, population-based, nonpharmacological approaches to pain management in primary care.